The Cultivation System in Banyuwangi’s Coffee Plantations in 1818-1829 - Fachri Zulfikar; Djono Djono; Susanto Susanto (Budapest International Research and Critics University, 2021)
This study discussed Banyuwangi’s Coffee Plantation in 1818-1829, and the dynamics of submission mandatory referred to the Priyangan (Preangerstelsel) system that affected the coffee plantations in Banyuwangi. This study used history as the research method. It shows the coffee journey from early planting and the ups and downs of coffee plantation income. To achieve the expected production, the Dutch East Indies government made some efforts, including reopening the abandoned Sukaradja plantations, opening a new plantation on the slopes of Idjen-Raung Mountain, and opening the citizen's gardens with a private system until a coffee fencing system. The coffee produced was Arabica/Djawa coffee, which became an excellent coffee in International scope. 1829 was the last year of the compulsory submission system, referring to the Priyangan system and changed to the cultivation system (Cultuurstelsel).